2022
DOI: 10.1111/jar.13068
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a telehealth exercise intervention on balance in adults with Down syndrome

Abstract: Background: People with Down syndrome often present with balance deficits, which compromise safety during daily activity. While evidence shows that exercise can improve balance in the Down syndrome population, it is unclear if a telehealth method will elicit similar benefits. We aimed to examine the effects of a virtual exercise program on balance in adults with Down syndrome.Methods: Eighteen low-active participants with Down syndrome completed a 12-week telehealth exercise program based on the Mann Method. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In addition, van Vugt et al [ 22 ] reported more effective results when the mobile phone app was incorporated into regular rehabilitation. Guerrero et al [ 24 ] examined the effects of a virtual exercise program on balance in adults with Down syndrome and reported a significant improvement compared with the pretesting level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, van Vugt et al [ 22 ] reported more effective results when the mobile phone app was incorporated into regular rehabilitation. Guerrero et al [ 24 ] examined the effects of a virtual exercise program on balance in adults with Down syndrome and reported a significant improvement compared with the pretesting level.…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates, the titles and abstracts of 289 publications were screened. Based on the inclusion and exclusion criteria, the full texts of 38 publications were read, 18 publications were excluded, and 20 publications were included in this review (Figure 1, Multimedia Appendix 1 [3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]). Among the 20 studies that reported the use of a device or app, 2 were related to anamnesis and subjective symptoms [3,8], 12 were related to objective examination [8][9][10][11][12][13][14][15][16][17][18][19], 7 were related to remote diagnosis [9,11,15,16,18,20], and 7 were related to treatment and rehabilitation [20][21][22][23][24]…”
Section: Overviewmentioning
confidence: 99%
“…The Mann Method™ PT exercise programme used for this study was an online, 12‐week integrative exercise programme developed and provided by a PT with extensive experience working with adults with DS (Sarah Mann, PT, DPT, MBA, NSCA‐CPT) (Guerrero et al . 2022; Mann et al . 2023).…”
Section: Methodsmentioning
confidence: 99%
“…The Mann Method ™ PT exercise programme used for this study was an online, 12-week integrative exercise programme developed and provided by a PT with extensive experience working with adults with DS (Sarah Mann, PT, DPT, MBA, NSCA-CPT) (Guerrero et al 2022;Mann et al 2023). Participants attended three virtual, live and interactive exercise sessions per week for a total of 12 weeks through the HIPAA-compliant version of Zoom.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation